Photovoltaic properties of ZnO nanorods/p-type Si heterojunction structures - Pietruszka, Rafal; Witkowski, Bartlomiej Slawomir; Luka, Grzegorz; Wachnicki, Lukasz; Gieraltowska, Sylwia; Kopalko, Krzysztof; Zielony, Eunika; Bieganski, Piotr; Placzek-Popko, Ewa; Godlewski, Marek (Beilstein Journal of Nanotechnology, 2014)
Selected properties of photovoltaic (PV) structures based on n-type zinc oxide nanorods grown by a low temperature hydrothermal method on p-type silicon substrates (100) are investigated. PV structures were covered with thin films of Al doped ZnO grown by atomic layer deposition acting as transparent electrodes. The investigated PV structures differ in terms of the shapes and densities of their nanorods. The best response is observed for the structure containing closely-spaced nanorods, which show light conversion efficiency of 3.6%.
Keywords: atomic layer deposition; hydrothermal method; solar cells; zinc oxide; zinc oxide nanorods